Livelihood diversification and rural-urban linkages in Vietnam’s Red River Delta - Thanh, Hoang Xuan; Anh, Dang Nguyen; Tacoli, Cecilia (International Food Policy Research Institute, 2005)
With high population density and limited land availability, Vietnam’s Red River Delta is undergoing a major transformation as its economic base moves away from subsistence farming towards intensive, high-value food production for export and local urban markets, and nonfarm employment. This paper describes the changing livelihoods of the residents of two villages that represent two different pathways to local economic development. One village relies primarily on agricultural intensification and diversification, although in combination with nonfarm activities. These nonfarm activities are either supplementary (such as handicraft production and seasonal migration) or related to farming, such as provision of agricultural services, transport and trade of agricultural produce. To a large extent, it is this nonfarm income that allows investment in agriculture at the household level. Residents of the second village, although nominally still owning rice farms, have effectively moved out of agriculture and engage almost exclusively in handicraft production. Despite these major differences, there are also important similarities between the two villages. First, much of their recent economic development is linked to access to markets — including proximity to local urban centers and to Hanoi (where demand from urban consumers and from exporting enterprises has increased substantially), a vastly improved road and transport system, and an excellent communications infrastructure. Second, each village has developed forward and backward linkages with their main production sector. Last but not least, local authorities have played an important role in supporting local economic development, providing infrastructure, training for handicraft production, and inputs for farmers. The long-term sustainability of economic growth and poverty reduction in the Red River Delta will largely depend on strengthening rural-urban linkages. This includes adopting regulations on land use that allow farmers to better respond to growing urban demand for high-value produce; incorporate more explicitly the needs of the handicraft micro-enterprises in existing and future policies and plans for rural industrialization; recognize and support the role of seasonal migration in rural local economic development; and address the changing planning and natural resource management needs of these urbanizing villages.